The Relevance of Nurcholish Madjid’s Hermeneutical Thought in Contemporary Indonesian Islamic Discourse - Siregar, Paisal; Arifinsyah, Arifinsyah; Zulkarnaen, Zulkarnaen (JIA (Jurnal Ilmu Agama), 2026)
This study aims to examine the relevance of Nurcholish Madjid's hermeneutical thinking in the development of contemporary Indonesian Islamic discourse. As one of the most influential Islamic reformers in Indonesia, Nurcholish Madjid offers a hermeneutical approach that emphasizes rationality, contextualization, and openness to universal values. His ideas regarding the importance of returning to the substance of Islamic teachings (al-rujūʿ ilā al-uṣūl) and his rejection of the sacralization of culture form the basis for re-reading religious texts in a fresher way that is more relevant to the challenges of modernity. This study uses a qualitative method based on literature review and data analysis with a contextual hermeneutic approach. The results show that Cak Nur's hermeneutics remain relevant in responding to Islamic issues such as pluralism, religious moderation, democracy, and the relationship between religion and the state. His approach not only enriches the methodology of Islamic interpretation but also offers a theological foundation for strengthening an inclusive and progressive Islam in Indonesia. This relevance makes Cak Nur's thoughts an important reference in building a dialogical, critical, and contextual Islamic discourse amid the dynamics of Indonesian Muslim society today. This article contributes to the expansion of hermeneutics as an interpretive framework capable of critically and contextually bridging religious texts with social reality. This article broadens the understanding of Cak Nur's thinking not merely as intellectual discourse, but as an operational paradigm relevant to the development of dialogical and transformative Islamic discourse amid the dynamics of contemporary Indonesian Muslim society.